A snapshot of HIV-1 genetic diversity in Dominican Republic in 2024: Predominance of the BCar lineage and first description of a CRF02-AG isolate - Lily Soto; Yoneira F. Sulbaran; Rossana C. Jaspe; Francisco Ureña; Yoel Garcia; Carmen Luisa Loureiro; Héctor R. Rangel; Flor H. Pujol (PLoS ONE, 2026)
Although a decrease in the incidence of HIV-1 infection has been observed in the Caribbean, the prevalence of this viral infection is still around 1% in Dominican Republic. It has been shown that the subtype B circulating in many of the Caribbean islands is indeed a subtype B which was introduced before the expansion of the B Pandemic lineage (B Pandemic ), which has been called the Caribbean B lineage (B Car ). The aim of this descriptive study was to provide a snapshot of the present circulation of HIV-1 subtypes and lineages in this island. Different regions of the HIV-1 genome were amplified by RT-PCR and sequenced for phylogenetic analysis of the viral isolates circulating in La Vega and Santiago de los Caballeros, Dominican Republic, in 2024. Of the 26 HIV-1 isolates, all but one belonged to the HIV-1 subtype B. Several genomic regions were evaluated for their suitability for the lineage assignment. In addition to the PR/RT region, which was previously shown to discriminate between the two lineages, the INT region also allowed the discrimination, but VIF with less performance. In contrast, the NEF region did not seem suitable for lineage discrimination. From the 25 HIV-1 subtype B isolates, the lineage could be assigned in 20, 17 of them (85%) belonging to the B Car lineage. The other HIV-1 isolate was found to be a CRF02-AG isolate. The complete genome showed that this isolate was related to isolates circulating in Africa and Europe.